An Investigative Study of Job Satisfaction in Bhakra Beas Management Board - Kumar, Suresh (Journal of Education and Vocational Research, 2011)
The present study deals with the empirical results regarding the study of job satisfaction in Bhakra Beas Management Board. The study is attempted to assess the job satisfaction and their means difference among various satisfaction levels. The satisfied and dissatisfied groups to job satisfaction mean difference is also attempted. The disruptive research method is found suitable for this purpose. Primary data has been assembled by employing questionnaire. A sample of 360 respondents was selected from all unit of organization. The content, construct and item to total correlation validity were established. Reliability of the instrument was justified through the calculation of cronbach’s (α) alpha coefficient. The test-retest measure of reliability coefficient for job satisfaction scale was found acceptable. The finding appears to be reasonably valid in view of the deplorable socio- economic conditions of the employees and their factors influencing job satisfaction.